Review for the Design and Experimental Study of a Coaxial Twin-rotor Mars Unmanned Aerial Vehicle - Zhifang Ke; Yu Hu; Qingkai Meng; Yongjie Shu; Jinghan Tu; Molei Zhao; Shiyi Wei; Haitao Zhang; Bin Xu; Zhaopu Yao; Wei Wei (Space: Science & Technology)
The thin atmosphere of Mars presents a necessary yet challenging flight environment for low-altitude flying vehicles or unmanned aerial vehicles. As a key technology, Martian unmanned aerial vehicles hold marked value and importance for scientific research and future interplanetary exploration. This review systematically explores the advantages and challenges of coaxial dual-rotor Martian drones under low-Reynolds-number conditions, focusing on the optimization of blade design methods and experimental research progress under these conditions. It also details the development of a multi-degree-of-freedom coaxial dual-rotor Martian drone prototype and its flight control algorithm strategy. In addition, the review describes the process of establishing a blade testing platform in a vacuum chamber to simulate the Martian environment. The review offers a comprehensive analysis of the different impacts that the environments of Earth and Mars have on the design of coaxial dual-rotor drones and looks forward to potential design methods and experimental research directions for future Martian drone development. Through takeoff experiments conducted in an Earth-based simulated Martian environment, the feasibility of flight testing for Martian drones is verified. The review compares the differences and characteristics of developing coaxial dual-rotor drones under terrestrial and Martian conditions, providing valuable examples and a solid foundation for the research and development of Martian drones.